A methodological review on bio-lubricants from vegetable oil based resources. (April 2017) - Panchal, Tirth M.; Patel, Ankit; Chauhan, D.D.; Thomas, Merlin; Patel, Jigar V.
Abstract: Finiteness of global crude oil reserve, rising crude oil prices, and issues related to environment seems to be a reality check for the problems of emerging generations. Present article focuses on lubricating oils as well as lubricating greases developed from vegetable oil. Vegetable oil based lubricants are an attractive alternative to conventional petro based lubricants due to number of their physical properties including renewability, biodegradability, high lubricity and high flash points. Still they have not yet replaced petro based lubricants due to their inappropriate chemical structure, which lags them behind at various odd conditions during applications. The challenges in this field are to improve certain characteristics of vegetable oils without impairing their excellent tribological and environmentally relevant properties. Chemical modification of vegetable oils overcomes the structural problems related to vegetable oils which in turn makes them fit for the application of lubricant. In this review article, we have reviewed the available literature and recently published data related to development of bio-lubricants by chemical modifications of vegetable oils.